Prevention of peritoneal adhesions using antioxidant complex in the experiment - V. I. Tikhonov; M. B. Plotnikov; S. V. Logvinov; M. Yu. Grishchenko; D. A. Shkatov; Ye. V. Semichev (Бюллетень сибирской медицины)
In the analysis of known ways to prevent adhesions, by which the proposed alternative effects on the formation of adhesions in the abdominal cavity. We analyze the effect of antioxidant complex formation of adhesions in the experiment.